2009
DOI: 10.1111/j.1365-2486.2009.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the disturbance hypothesis explain the biomass increase in basin‐wide Amazon forest plot data?

Abstract: Positive aboveground biomass trends have been reported from old-growth forests across the Amazon basin and hypothesized to reflect a large-scale response to exterior forcing. The result could, however, be an artefact due to a sampling bias induced by the nature of forest growth dynamics. Here, we characterize statistically the disturbance process in Amazon old-growth forests as recorded in 135 forest plots of the RAINFOR network up to 2006, and other independent research programmes, and explore the consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 28 publications
1
77
0
1
Order By: Relevance
“…Terrestrial ecosystems and, in particular, tropical forests have been recognized as strong carbon sinks, comparable to the oceans (132)(133)(134). However, the potential connections between sinks of carbon and the spatial patterns of soil and tree characteristics across the region are also noteworthy.…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
“…Terrestrial ecosystems and, in particular, tropical forests have been recognized as strong carbon sinks, comparable to the oceans (132)(133)(134). However, the potential connections between sinks of carbon and the spatial patterns of soil and tree characteristics across the region are also noteworthy.…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
“…Fisher et al (2008) also use a flawed procedure to fit the size distribution of disturbance events, and thus almost certainly overestimate the probability of large disturbance events. Gloor et al (2009) corrected these errors, and concluded that sample sizes in area and time were sufficient to demonstrate that average biomass change in 135 forest plots, typically 1 ha or larger, across the Amazon basin is significantly positive, under the assumptions that plots were an unbiased sample of the landscape and that individual plot biomass change estimates were unbiased. It is important to note that these results are sensitive to the frequency of large disturbance events, and that there are very limited existing data relevant to estimating these frequencies.…”
Section: E T E C T I N G a N D P R O J E C T I N G C H A N G E S I mentioning
confidence: 99%
“…Fisher et al (2008) and Gloor et al (2009) recently explored the influence of sampling error on true power to reject the null hypothesis of no change in biomass given the potential for large-scale disturbances. These studies use simulation analyses to explore the importance of clustered disturbances combined with the 'slow in, rapid out' nature of biomass change, and the sample size needed to confidently reject a null hypothesis of no change.…”
Section: E T E C T I N G a N D P R O J E C T I N G C H A N G E S I mentioning
confidence: 99%
See 2 more Smart Citations